The Role of Human Dignity Philosophy in TVET Student Representative Council - Mohd Junaidi, Nurul Hidayah; Hamid, Hashima (Online Journal for TVET Practitioners, 2025)
The philosophy of human dignity plays a vital role in shaping leadership within Technical and Vocational Education and Training (TVET) institutions, particularly in the context of Student Representative Councils (SRC). This conceptual paper explores how the integration of human dignity principles, enhances the effectiveness of SRC in TVET settings. Drawing on leadership theories and the challenges faced by young leaders, especially in terms of biases and limited authority, the paper examines how SRCs can foster ethical decision-making and student engagement by upholding human dignity. It also discusses the moderating influence of transformational leadership, emphasizing that leadership practices that inspire, challenge, and include all students can significantly improve the outcomes of human dignity-centered leadership. By embracing these principles, SRC can cultivate an environment where student voices are valued, and future leaders are prepared to engage ethically and inclusively in both academic and societal contexts.